Anti-aggregant therapy effectiveness among coronary heart disease patients in late post-bypass surgery period - O. F. Kardash; L. G. Gelis; I. V. Gugnina; Yu. P. Ostrovsky (Российский кардиологический журнал)
In 98 coronary heart disease (CHD) patients, who underwent complete myocardial revascularization, the effectiveness of anti-aggregant therapy with aspirin and thienopyridines, as well as cell hemostasis parameters, were evaluated in the first post-intervention year. Platelet aggregation was assessed with turbidimetric method, using ADP di-Na salt. Treatment effectiveness was assessed by end-points (death, myocardial infarction, recurrent angina, re-intervention). Statistical analysis was performed with Excel 7.0 program pack. Stable inhibition of platelet function was achieved with thienopyridine treatment. Low functional platelet activity was associated with reduced risk of adverse events in CHD patients who underwent bypass surgery, without significant difference between aspirin-sensitive and thienopyridine groups (p=0,176). Adverse event risk was increased in late post-intervention period among patients with normo- or hyper-aggregation cell hemostasis, who received aspirin monotherapy. Therefore, aspirin is effective for secondary prevention after bypass surgery, but its routine administration is not recommended when no cell hemostasis effect is observed.